Training and Hedonic Survey Tests of Herbal Bath Salt Products with a Combination of Jeringau and Lemon Peel as a Body Relaxant - Utami, Nurhafizah; Surbakti, Chemayanti; Lubis, Muhammad Fauzan; Juwita, Nur Aira (Talenta Publisher, 2023)
Bath salt or better known as bath salt is a product that has recently been growing rapidly. Herbal bath salt itself is still not widely developed by the community. Herbal bath salts can be made from ginger powder and lemon peel which has a distinctive fragrance that can be relaxing for anyone who uses it. This community service activity involved class XI HKBP Sidorame Private High School students based on an innovative herbal bath salt preparation with a combination of ginger and lemon peel. The purpose of this activity is to determine the level of preference (hedonic) for a combination of lemon peel and ginger bath salt preparations. The activity began with the preparation of a combination of lemon peel and ginger bath salt. The activity ended with data collection using pre-test, post-test and hedonic test questionnaires. The results of filling out the pre-test showed that SMAS HKBP Sidorame students' knowledge was still lacking with the proportions for each question namely 23,33%, 6,66%, 10%, 0% and 30%. The results of filling out the post-test showed that the students' knowledge of SMAS HKBP was very good with a proportion of 100% for each question. This shows the development and increase in knowledge of SMAS HKBP Sidorame students about bath salts. The results of the hedonic test survey obtained the largest proportion for shape parameters of 56,66% (very like), color of 50% (like very much), fragrance of 70% (very like), hardness of 46,66% (very like) and ease of use of 63,33% (very like). These results indicate that SMAS HKBP Sidorame students like bath salt product.